2010
DOI: 10.1111/j.1464-410x.2010.09436.x
|View full text |Cite
|
Sign up to set email alerts
|

The index lesion and focal therapy: an analysis of the pathological characteristics of prostate cancer

Abstract: RESULTSOverall, 374 foci were examined. The median number of tumours per patient was 3.5 (range 1-15). The overall median tumour volume was 1.4 mL (range 0.1-18.2), the median volume of the largest (index) tumour was 0.95 mL (range 0.1-18.2) and the median volume of the largest secondary tumour was 0.2 mL (range 0.05-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 23 publications
0
60
0
2
Order By: Relevance
“…Several studies have yielded similarly discouraging results [18,19]. There have been interesting reports from groups investigating the possibility of administering focal therapy in cases where only insignificant tumours exist contralaterally to the index tumour [20,21]. The situation where only insignificant disease exists in addition to the index tumour can be described as biologically unifocal as opposed to anatomically unifocal disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have yielded similarly discouraging results [18,19]. There have been interesting reports from groups investigating the possibility of administering focal therapy in cases where only insignificant tumours exist contralaterally to the index tumour [20,21]. The situation where only insignificant disease exists in addition to the index tumour can be described as biologically unifocal as opposed to anatomically unifocal disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic acquisition over the pelvis followed by a whole-body PET or PET/CT static acquisition including the pelvis has been proposed as allowing visualization of pelvic disease without interference from bladder uptake (dynamic imaging) while allowing maximum sensitivity for distant disease (delayed whole-body PET or PET/CT). 20,21,24,34,35,37,38,42,57 Early time points for imaging (0-15 min post-intravenous injection) and/or delayed imaging time points (30,40,45,60, 90-120 and 65-200 min post-intravenous injection) have been also described in the published literature. 22,23,[27][28][29][30][31][32][33]36,39,40,41,[43][44][45][46][47][48][49][50][51][52][54][55][56] 34 16…”
Section: Methodsmentioning
confidence: 99%
“…In PCa patients under hormone therapy, 18 F-fluorocholine for prostate cancer imaging G Bauman et al have one or two dominant intra-prostatic lesions (DILs) suggest lesions that could serve as a target for focal dose escalation. 60,61 Such a strategy requires accurate localization of DILs through combinations of biopsy information and imaging. 62 Pinkawa et al 49 described the use of 18 F-FCH PET/CT for delineation of DILs in radiation treatment planning for 66 PCa patients.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…It is hypothesized that the index lesion (largest tumor volume within the prostate) and occasionally a secondary index lesion will determine the biological potential of the cancer. Bott et al 7 reported that the index lesion comprised 73% of tumor volume in a total of 374 tumor foci examined. This has led to considering a more preservative approach to treating prostate cancer, including hemi-ablation (half-gland treatment) and focal ablation.…”
Section: Evaluation Of Patients For Focal Therapymentioning
confidence: 99%